Abnormal rise of surface temperature In association with thunderstorm downdrafts (MAUSAM, 1969)
In association with downdrafts from thunderclouds, an abrupt and abnormal rise in surface temperature of the order of 5 to 60C  was recorded at Nagpur and Visakhapatnam on two different days during summer season and with this abrupt rise, the surface temperature touched once again the day’s maximum temperature at these two places recorded earlier in the afternoon. These two cases are described in this paper and a plausible explanation for the abrupt rise in temperature is also presented.